Urban green spaces in determining the house price: a theoretical framework - Asmawi, M. Zainora; Hj. Mohd. Noor, Norzailawati; Manzahari, Mohd Nasrul Hanis (2014)
Over the years, there is an obvious loss of green spaces in Kuala Lumpur in order to give ways for more developments. As a result, the reduction of green elements could affect the quality of life of urban dwellers. Urban green areas as environmental goods are essential to support the quality of life. As there are mixed evidences on the relationship between green spaces and house price, this paper attempts to set up a framework to consider the importance of green areas in the housing market. The literatures present particularly at the international level that the relationship exists either in positive or negative pattern. Thus, this paper mainly focuses on the theoretical framework of considering green spaces as a factor determining house price in Kuala Lumpur. Several steps have been carried out during the preliminary study which included literature review, questionnaire survey, site observation and GIS application. In order to study how green spaces could be considered as a factor determining house price, the definition of green spaces has been narrowed down to open spaces, a sub-type of green spaces due to fact that open spaces are easier to recognize and survey. The effect of green spaces in determining house price can be surveyed by analyzing the relationship between the proximity of open space from specific house with the offered price surveyed from the house owners through questionnaire survey. The tilization of GIS can assist in providing a reliable set of results which requiring the availability of information on existing land use, urban pattern identification and computation of landscape metrics. This paper has dentified significant point which is - it is possible for green spaces to influence the house pricing in Kuala Lumpur. The theoretical framework and methods presented in this paper appear practical, workable and reasonable to obtain reliable results in future stages of the research.